Drug Resistance to Inhibitors of the Human Double Minute-2 E3 Ligase is Mediated by Point Mutations of p53, but can be Overcome with the p53 Targeting Agent RITA - Jones, Richard J. (2012)
The human double minute (HDM)-2 E3 ubiquitin ligase plays a key role in p53 turnover, and has been validated pre-clinically as a target in multiple myeloma (MM) and mantle cell lymphoma (MCL). HDM-2 inhibitors are entering clinical trials, and we therefore sought to understand potential mechanisms of resistance in lymphoid models. Wild-type p53 H929 MM and Granta-519 MCL cells resistant to MI-63 or Nutlin were generated by exposing them to increasing drug concentrations. MI-63-resistant H929 and Granta-519 cells were resistant to Nutlin, while Nutlin-resistant cells displayed cross-resistance to MI-63. These cells also showed cross-resistance to bortezomib, doxorubicin, cisplatin, and melphalan, but remained sensitive to the small molecule inhibitor RITA. HDM-2 inhibitor-resistant cells harbored increased p53 levels, but neither genotoxic nor non-genotoxic approaches to activate p53 induced HDM-2 or p21. Resequencing revealed wild-type HDM-2, but mutations were found in the p53 DNA binding and dimerization domains. In resistant cells, RITA induced a G(2)/M arrest, up-regulation of p53 targets HDM-2, PUMA, and NOXA, and PARP cleavage. Combination regimens with RITA and MI-63 resulted in enhanced cell death compared to RITA alone. These findings support the possibility that p53 mutation could be a primary mechanism of acquired resistance to HDM-2 inhibitors in MCL and MM. Furthermore, they suggest that simultaneous restoration of p53 function and HDM-2 inhibition is a rational strategy for clinical translation.